MATH SOLVE

3 months ago

Q:
# Nathaniel writes the general form of the equation gm = cm + rg for when the equation is solved for m. He uses the general form to solve the equation –3m = 4m – 15 for m. Which expression shows what Nathaniel will actually evaluate? 4 + 15 – 3 4 – 15 + 3 –15 –

Accepted Solution

A:

Answer:The required expression is [tex]m=\frac{-15}{-3-4}[/tex].Step-by-step explanation:The general form of the equation is[tex]gm=cm+rg[/tex] .... (1)We need to solve this equation for m.Subtract cm from both the sides.[tex]gm-cm=rg[/tex]Taking out the common factor.[tex]m(g-c)=rg[/tex]Divide both sides by (g-c).[tex]\frac{m(g-c)}{g-c}=\frac{rg}{g-c}[/tex][tex]m=\frac{rg}{g-c}[/tex] ..... (2)The given equation is[tex]-3m=4m-15[/tex] ..... (3)From (1) and (3), we get[tex]g=-3,c=4,rg=-15[/tex]Substitute g=-3, c=4, rg=-15 in equation (2).[tex]m=\frac{-15}{-3-4}[/tex]Therefore the required expression is [tex]m=\frac{-15}{-3-4}[/tex].